State Merit-Aid Programs and College Major: A Focus on STEM - David L. Sjoquist; John V. Winters (Institute for the Study of Labor (IZA), 2013)
Since 1991 more than two dozen states have adopted merit-based student financial aid programs, intended at least in part to increase the stock of human capital by improving the knowledge and skills of the state's workforce. At the same time, there has been growing concern that the U.S. is producing too few college graduates in science, technology, engineering, and mathematics (STEM) fields. Using both microdata from the American Community Survey and student records from the University System of Georgia, this paper examines whether recently adopted state merit-aid programs have affected college major decisions, with a focus on STEM fields. We find consistent evidence that state merit programs did in fact reduce the likelihood that a young person in the state will earn a STEM degree.
Keywords: I23; J24; 330; merit aid; HOPE scholarship; college major; STEM